Intercultural competences of the professional serum health - Chávez Agurto, Patricia (2022)
Introduction. Given the cultural plurality, populations with varied conceptions of health and disease and multiple ways of understanding them coexist, where the differences in access to health are influenced by the limited capacity of the health professional to attend populations from different cultures, making it necessary to put intercultural competencies into practice. Objective. To determine the intercultural competencies of the serumist health professional. Methods. A descriptive observational study was undertaken in a nonprobabilistic sample of 48 serum health professionals in 3 districts of the Province of Puerto Inca, Huanuco Region, Peru. Information was collected using the survey technique, and the questionnaire was used as an instrument, with different response options previously validated by expert judgment. Reliability with Cronbach’s alpha coefficient. Data analysis with descriptive statistics, recorded in graphs and tables, processed with the statistical software SPSS 25. Results. Intercultural competencies are not developed in the curricular plans. Conclusions. The participants of the study considered that the subjects of the curricular plan do not favor the development of these intercultural competencies; they are not prepared to interact in these contexts different from the one in which they have been trained.